Genetic Variation in the Prostate Stem Cell Antigen Gene and Upper Gastrointestinal Cancer in White Individuals - Lochhead, Paul; Frank, Bernd; Hold, Georgina L.; Rabkin, Charles S.; Ng, Michael T.H.; Vaughan, Thomas L.; Risch, Harvey A.; Gammon, Marilie D.; Lissowska, Jolanta; Weck, Melanie N.; Raum, Elke; Müller, Heiko; et al. (Gastroenterology (New York, N.Y. 1943), 2011)
An association between gastric cancer and the rs2294008 (C>T) polymorphism in the prostate stem cell antigen ( PSCA) gene has been reported for several Asian populations. We set out to determine whether such an association exists in white individuals. We genotyped 166 relatives of gastric cancer patients, including 43 Helicobacter pylori-infected subjects with hypochlorhydria and gastric atrophy, 65 infected subjects without these abnormalities, 58 H pylori-negative relatives, and 100 population controls. Additionally, a population-based study of chronic atrophic gastritis provided 533 cases and 1054 controls. We then genotyped 2 population-based, case-control studies of upper gastrointestinal cancer: the first included 312 gastric cancer cases and 383 controls; the second included 309 gastric cancer cases, 159 esophageal cancer cases, and 211 controls. Odds ratios were computed from logistic models and adjusted for confounding variables. Carriage of the risk allele (T) of rs2294008 in PSCA was associated with chronic atrophic gastritis (adjusted odds ratio [OR], 1.5; 95% confidence interval [CI]: 1.1–1.9) and noncardia gastric cancer (OR, 1.9; 95% CI: 1.3–2.8). The association was strongest for the diffuse histologic type (OR, 3.2; 95% CI: 1.2–10.7). An inverse association was observed between carriage of the risk allele and gastric cardia cancer (OR, 0.5; 95% CI: 0.3–0.9), esophageal adenocarcinoma (OR, 0.5; 95% CI: 0.3–0.9), and esophageal squamous cell carcinoma (OR, 0.4; 95% CI: 0.2–0.9). The rs2294008 polymorphism in PSCA increases the risk of noncardia gastric cancer and its precursors in white individuals but protects against proximal cancers.